2018
DOI: 10.1007/s00464-018-6422-7
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted versus laparoscopic Roux-en-Y gastric bypass and sleeve gastrectomy: a propensity score-matched comparative analysis using the 2015–2016 MBSAQIP database

Abstract: Our findings show that postoperative bleeding and blood transfusion are significantly reduced with the robotic platform, and after correcting for all factors including operative time, the robotic-assisted approach is associated with better postoperative outcomes especially for RYGB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
17
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 40 publications
9
17
0
1
Order By: Relevance
“…With regard to complications, our results confirm other original papers [13,15,17,28] and meta-analysis [21,22]. Economopoulos found fewer reoperations and strictures after using the robot [21].…”
Section: Discussionsupporting
confidence: 89%
“…With regard to complications, our results confirm other original papers [13,15,17,28] and meta-analysis [21,22]. Economopoulos found fewer reoperations and strictures after using the robot [21].…”
Section: Discussionsupporting
confidence: 89%
“…More recently, our group showed a similar rate of SAE when comparing robotic and laparoscopic RYGB patients based on the more recent 2016 MBSAQIP data file [19]. Similarly, using 2015 to 2016 MBSAQIP data, Sebastian et al [16] demonstrated decreased length of stay, anastomotic leak, and renal complications for robotic RYGB patients after accounting for operative time and conversion rate. The sleeve patient cohort also showed improvement in bleeding and stricture rates with the robotic platform.…”
Section: Discussionsupporting
confidence: 57%
“…The safety of the robotic platform in bariatric surgery has been previously established [13,14]. Despite the established safety of robotics in bariatric surgery, the main disadvantages continue to be increased operating time and cost [15][16][17], as well as increased readmissions, which indicates greater resource utilization [17]. In addition, the safety and benefit of robotics in SO patients has been poorly reported, although single-institutional data with small sample sizes have shown that robotic surgery is safe in this patient population, with comparable results to both open and laparoscopic approaches [12].…”
Section: Discussionmentioning
confidence: 99%
“…Robotic sleeve gastrectomy reduced the postoperative bleeding (0.16% vs. 0.43%; p < 0.001) and stricture (0.19% vs. 0.33%; p = 0.04) significantly when compared with traditional laparoscopic sleeve gastrectomy. 1,2,14,15 In review of the literature, no significant difference of the operative time was found between totally-robotic RYGB and laparoscopic RYGB (p = 0.42). On the other hand, there was increased operative time for roboticassisted RYGB versus laparoscopic RYGB (158.29 ± 65 vs. 120.17 ± 56; P < 0.001), and for robotic sleeve gastrectomy compared with laparoscopic sleeve gastrectomy (102.58 ± 46 vs. 73.38 ± 36; P < 0.001).…”
Section: Laparoscopic Versus Robotic Approach To Bariatric Surgerymentioning
confidence: 96%
“…Finally, we believe that the operative time in robotic approach can be reduced once the learning curve is overcome, just as with other robotic procedures. 1,[13][14][15] Although robotic procedures seem to be more expensive than laparoscopic surgery due to initial purchase costs of the robot and the robotic instruments and accessories, as well as yearly maintenance fees that are associated with significant costs. From the University Health System Consortium (UHC) Clinical Database, the mean cost of robotic gastric bypass was $12,670, versus $10,105 for laparoscopic RYGB (p < 0.05).…”
Section: Laparoscopic Versus Robotic Approach To Bariatric Surgerymentioning
confidence: 99%